Early evidences of links between soil microbes and forest restoration through multiple ecosystem metrics - Vivian, Jenny; Chazdon, Robin L.; Catling, Alexandra A.; Lee, David J. (Frontiers in Forests and Global Change, 2025)
Forest restoration influences several complementary ecosystem features and their trajectories, which ultimately can lead to diverse outcomes. However, integrated assessments of above- and below-ground responses to restoration efforts are lacking. For this reason, we conducted a review assessing advances in monitoring forest restoration, including the role of soil microbes in forest development. We reviewed advances in integrated forest restoration assessments measuring plant diversity, vegetation structure, ecosystem functions, and soil microbial communities based on environmental DNA. We also explored how considering soil microbial dynamics can improve restoration practices. Using the Scopus database, we searched for articles on forest restoration assessment that included the ecosystem features listed above. We extracted the location, biome, methodology and findings of each study. The novelty of the integrated approach was highlighted by the presence of a scattered and biased number of studies. Only 17 articles (out of 30) evaluated all the searched parameters together, with 14 of these studies being based in China. Microbial taxonomic diversity was affected by soil chemistry, plant diversity, and vegetation structure. Bacteria taxa richness fluctuated over time, whereas fungal taxa richness demonstrated hump-shaped and site-specific responses to forest restoration and tree community succession. Over time, bacteria functional groups’ relative abundance shifted from oligotrophic to copiotrophic taxa dominance, while for the fungal groups, the dominance changed from saprophytic to ectomycorrhizal in different forest biomes. This review provides general insights into the advances of restoration assessments considering microbial communities and the utility of analyzing multiple parameters to understand microbial community responses which, in turn, affect restoration outcomes.